2009
DOI: 10.1039/b917900c
|View full text |Cite
|
Sign up to set email alerts
|

A photochemically initiated chemistry for coupling underivatized carbohydrates to gold nanoparticles

Abstract: The sensitive optoelectronic properties of metal nanoparticles make nanoparticle-based materials a powerful tool to study fundamental biorecognition processes. Here we present a new and versatile method for coupling underivatized carbohydrates to gold nanoparticles (Au NPs) via the photochemically induced reaction of perfluorophenylazide (PFPA). A one-pot procedure was developed where Au NPs were synthesized and functionalized with PFPA by a ligand-exchange reaction. Carbohydrates were subsequently immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 44 publications
(67 reference statements)
3
149
3
1
Order By: Relevance
“…81 a) b) Wang et al found that the sensitivity of mannose-functionalised nanoparticles towards ConA increased with the spacer length. 82 The authors prepared the glyconanoparticles using a photocoupling method, as previously described in this review, 66 and more flexible spacer linkage exhibited the lowest limit of detection. 82 While these results appear to contradict previous work, 52,76,78 it is possible that the flexibility of the anchor chain is an additional important feature for the targeting and sensitive detection of proteins with glyconanoparticles.…”
Section: Length Of the Anchor Chain That Tethers The Carbohydrate To mentioning
confidence: 99%
See 2 more Smart Citations
“…81 a) b) Wang et al found that the sensitivity of mannose-functionalised nanoparticles towards ConA increased with the spacer length. 82 The authors prepared the glyconanoparticles using a photocoupling method, as previously described in this review, 66 and more flexible spacer linkage exhibited the lowest limit of detection. 82 While these results appear to contradict previous work, 52,76,78 it is possible that the flexibility of the anchor chain is an additional important feature for the targeting and sensitive detection of proteins with glyconanoparticles.…”
Section: Length Of the Anchor Chain That Tethers The Carbohydrate To mentioning
confidence: 99%
“…Aggregation studies in the presence of ConA were performed to investigate whether the recognition ability of the carbohydrates changes upon coupling. 66 The coupling of carbohydrates using microwave radiation is another alternative for the functionalisation of gold nanoparticles. 68 In this example, gold nanoparticles were first functionalised with di(N-succinimidyl)3,3'-dithiodipropionate and then reacted with 2-mercaptoethylamine hydrochloride via succinimidyl-amino covalent binding.…”
Section: Assembly Of the Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic photoluminescence of quantum dots has been utilized for specific protein sensing [68,69]. Composites of the aforementioned gold NP, silver NP and quantum dots usually with silica or polymeric materials have also been employed as described in a recent review [70] The multivalent presentation of carbohydrate ligands significantly enhances the binding affinity toward lectins by several orders of magnitude in comparison to the free ligands in solution and strongly depends on the type and length of the spacer linkage and ligand density [71].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Considering the fact that many of the currently known CRDs only bind to the terminal oligosaccharides of glycans, glycopolymers with repeating pendent units show their great advantage in mimicking these terminal oligosaccharides [9][10][11][12], which is important to further exploration on both of the known and unknown carbohydrate-protein interactions. Meanwhile, the artificial glycopolymers and glyco-nanoparticles have show enhancement multivalent binding behavior of carbohydrate and lectins [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%